2009
DOI: 10.5194/angeo-27-2971-2009
|View full text |Cite
|
Sign up to set email alerts
|

The electron density of Saturn's magnetosphere

Abstract: Abstract.We have investigated statistically the electron density below 5 cm −3 in the magnetosphere of Saturn (7-80 R S , Saturn radii) using 44 orbits of the floating potential data from the RPWS Langmuir probe (LP) onboard Cassini. The density distribution shows a clear dependence on the distance from the Saturnian rotation axis (as well as on the distance from the equatorial plane (|Z|), indicating a disclike structure. From the characteristics of the density distribution, we have identified three regions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 36 publications
9
93
0
Order By: Relevance
“…The periodicity of these heavy rich events was found to be close to the southern SKR period. Morooka et al (2009) have shown that quasiperiodic variations of the electron density can be observed all over the magnetosphere, even in the lobe region beyond L = 15. They also found that Saturn's magnetosphere has a strong longitudinal asymmetry.…”
Section: Introductionmentioning
confidence: 96%
“…The periodicity of these heavy rich events was found to be close to the southern SKR period. Morooka et al (2009) have shown that quasiperiodic variations of the electron density can be observed all over the magnetosphere, even in the lobe region beyond L = 15. They also found that Saturn's magnetosphere has a strong longitudinal asymmetry.…”
Section: Introductionmentioning
confidence: 96%
“…[3] Although various particle and field observations in Saturn's magnetosphere showed periods similar to the SKR modulation [Espinosa and Dougherty, 2000;Carbary et al, 2007;Morooka et al, 2009], it was only recently that the northern and southern SKR periods have been identified in other data. In particular, Andrews et al [2010] showed that the north and south SKR periods correspond to the rotation periods of quasi-dipolar magnetic field perturbations observed at high latitudes over the northern and southern polar regions, and Nichols et al [2010] showed that the two SKR periods are the same as the periods of dawn-dusk oscillations of the northern and southern auroral ovals as viewed by the Hubble Space Telescope (HST).…”
Section: Introductionmentioning
confidence: 99%
“…This periodicity can cause a larger variability at Titan than the solar wind (cf. Persoon et al, 2005Persoon et al, , 2006Morooka et al, 2009). Simon et al (2010a) classified the first 62 Titan flybys as lobe-type or current sheet.…”
Section: Introductionmentioning
confidence: 99%